Faktor yang Mempengaruhi Kurangnya Minat Baca Peserta Didi Dalam Pembelajaran Bahasa Indonesia di SD Negeri 24 Kalumbuk - Fanza, Aulia My Love; U, Ulfatmi; Yufita, Anjeli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Low reading interest of learners in primary schools is a serious problem that directly impacts the quality of learning, especially in Bahasa Indonesia subjects. This article aims to identify and analyze various factors affecting learners’ low reading interest through a literature review approach. The analysis results show that the factors include limited literacy facilities, lack of active role of teachers and parental support, negative influence of digital technologies, less interesting teaching methods, as well as low motivation and reading habits of students. The impact of low interest in reading includes reading comprehension difficulties, weak vocabulary acquisition, and low learning achievement. The article also reviews various strategies that teachers can implement to increase students’ reading interest, such as reading habituation, use of storytelling methods, reading prompts, use of technology, as well as thematic approaches and creative literacy programs. Collaboration between schools, families, and communities is essential to create a literacy ecosystem that supports the growth of an early interest in reading.